Gandhi [videorecording] - Cameron, James; Lagone, Patricia (Heroes and tyrants of the twentieth century series, 1990)
Looks at this remarkable man who single-handedly freed India from British Nile. Containing footage of Gandhi's Salt March to the sea, his famous London address, and his brutally candid interviews, it brings Gandhi's immortal message of non-violence and love.